Train Network Performance Test Method Based on RFC 2544 Standard - CHEN Chaoqun; CHEN Bo (机车电传动)
Aiming at the problem that there was no clear way to test the train communication network performance at present, based on the RFC 2544 standard, the performance testing of Ethernet based on train formation network was studied, and the Ethernet performance testing environment was built. The simulation results showed that the scheme could support a variety of topology and configuration, and accurately test the performance of the train network, which could provide support and basis for the further development of the train real-time Ethernet.